Technology of Welding Metal Products Under Flux Layer - PhD student Begmatov D.K; PhD student Khaydarov U.Y (Genius Journals, 2022)
This article provides information on the technology of welding of metal products under the seam or superfluous layer of flux, its advantages and disadvantages, the brands of fluxes used in welding. The method of welding under the flux layer was also compared with other welding methods.
Keywords: Metal; Copper; Bronze; Lead